TINGKAT MOTIVASI PETANI DALAM USAHATANI NILAM DI DESA KECAMATAN ANGATA KABUPATEN KONAWE SELATAN - Muh. Arisanto; Rosmawaty Rosmawaty; Suriana Suriana (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2023)
The goal of this study was to determine the level of intrinsic and extrinsic motivation of patchouli farmers. This research is located in Puulipu Village, Angata District, South Konawe Regency because the majority of the population works as patchouli farmers and is one of the largest patchouli oil suppliers in Angata District. This research was carried out from October 2022 to January 2023. The data obtained was analyzed quantitatively using the class interval formula. The results of the study found that the level of intrinsic motivation of farmers which includes the expectation of a pleasant job, social needs, and economic needs in running patchouli farming is classified in the high category. This happens because most of the needs and expectations of farmers in patchouli farming have been fulfilled. The level of extrinsic motivation of farmers which includes the availability of facilities and infrastructure, market opportunities, and innovation in patchouli farming is also relatively high. So that farmers are encouraged to increase their patchouli farming.